Testing the Anti-Bacterial Activity of Star Gooseberry Leaves (Souropus Androgynus L) Using the Disc Diffusion Method Using the n-Hexane Fraction Against Propionic Bacterium Acnes - Devita Riafinola Andaririt; Ardi Broto (Universitas STRADA Indonesia, 2023)
Acne vulgaris or acne, is a common inflammatory condition in the polysebaceous unit that occurs in teenagers and young adults and is characterized by comedones, papules, pustules, and nodules. One of the factors that causes acne is the Propionic bacterium acnes bacteria. One type of plant with antibacterial properties for acne is the Star Gooseberry Leaf plant (Souropus Androgynus L), which contains alkaloids, saponins, tannins, and flavonoids that act as antibacterials. Susanti (2012). This research aimed to obtain data on the antibacterial activity of the compound components contained in the n-hexane fraction of Star Gooseberry Leaves (Souropus Androgynus L) against the Propionic bacterium acnes bacteria, which can be seen from the inhibition zone. The method used was disc diffusion with three groups of control, namely (K(S), K(+), and K(-)). The test bacteria Propionic bacterium acnes, where the Control Sample consists of 4 test concentrations, namely 30 mg, 60 mg, 120 mg, and 240 mg. The positive control used two µg/disc Clindamycin, while the negative control was 2% DMSO. The results of the disc diffusion test of the ethanol fraction of Star Gooseberry Leaves (Souropus Androgynus L) using the disc diffusion method with concentrations of 30 mg/ml and 60 mg/ml did not provide an inhibition zone, the concentration of 120 mg/ml was 11.1 ± 0.10 mm, the concentration was 240 mg/ml was 14.63 ± 0.25 mm. The negative control DMSO 2% did not provide an inhibitory zone diameter, whereas the positive control Clindamycin 2 µg/disk provided an inhibition zone of 25.47 ± 0.70 mm.